Gambaran Kekerasan dan Penghayatan Imajinatif dalam Beberapa Karya Sastra Indonesia dan Perancis - P, Sumarwati Kramadibrata (UI Scholars Hub, 2003)
Description of violence against women in world literature has been found for long. As a social institution, it has proved itself as a significant medium to reflect problems of humanity, particularly the practice of violence against women. On the other hand, what the novelists depict can be regarded as a social critic or social control against what is happening around, besides as an imaginative insight of moral values or of ideology, even as a sort of therapeutic form. Violence itself appears in various forms, some explicitly described, others in perfect diguise.